Pemerintahan Susilo Bambang Yudhoyono dan Politik Luar Negeri Indonesia - Inayati, Ratna Shofi (Jurnal Penelitian Politik, 2005)
In his early presidential time President SBY took a series of visits to Australia, New Zealand and East Timor following his visit to Malaysia and Singapore a month before as his first step to start the Indonesian Diplomacy. In the next step, he also prepare to visit US and EU during May 2005. It indicates that President SBY still continues the basic strategy in the implementation of Indonesian Foreign Policy by President Megawati. Since the New Order govemment, Indonesia has adopt the Concentric Circle Formula as the base theory in the implementation of Indonesian Foreign Policy, putting emphasis on relation with countries within a series of concentric circles. The first concentric circle is ASEAN which is regarded as the comer stone of Indonesian foreign policy.The second circle, Indonesia puts a special emphasis on promoting relations with it’s Eastern and Southern neighbour, bringing Indonesian engagement with the Pacific Islands Forum, The South West Pacific Dialogue and the Tripartite Consultation between Indonesia, Australia and East Timor. Within the second concentric circle also includes Japan, China and South Korea in the ASEAN +3 forum.Beyond that, Indonesia puts in important attention to the relation with its major economic partners as US and EC, as regarded as the third concentric circle.